POLEMIK AL-ASMÂ AL-HUSNÂ DALAM AL-QUR`AN (Dimensi Feminin dan Maskulin) - Hilmi, Ahmad Alwan (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
The purpose of this study is to describe the duality that exists in al-asmâ al-ẖusnâ which contradicts one another. Such as the nature of al-Qâbidh (The Most Narrowing) but also al-Bâsith (The Most Expanding), al-Khâfidh (The Most Humbling) paradox with ar-Râfi’ (The Most Elevating). This study uses a qualitative method with descriptive-analysis by explaining in full about al-asmâ al-ẖusnâ. Then analyze it using the maudhû’i method, namely collecting verses related to al-asmâ al-ẖusnâ and connecting one verse to another with a comprehensive correlation. After that, the author looks for the meaning of each al-asmâ al-ẖusnâ. The results of this study are that in the periodization of revelation using the theory of revelation in the Qur'an, Allah informs or emphasizes more on His jamâliyah attributes than on His jalâliyah attributes. This can generally be resolved by understanding that the attributes of Allah are not contradictory to one another, but complementary. The attributes of compassion (ar-raẖmân) and the attributes (al-muntaqim) of Allah are not contradictory, but mutually supportive, so that, if sometimes they appear contradictory from a limited human perspective, but in a broader view, the two attributes are combined and harmonious in the greatness of Allah. Al-asmâ al-ẖusnâ seems paradoxical because human understanding is still partial, not comprehensive. It is not the attributes of Allah that are contradictory, but human understanding of Allah is partial. As a result, it seems as if there is a paradox in His names.